Are Pornography and Marriage Substitutes for Young Men? - Michael Malcolm; George S Naufal (Institute for the Study of Labor (IZA), 2014)
Substitutes for marital sexual gratification may impact the decision to marry. Proliferation of the Internet has made pornography an increasingly low-cost substitute. We investigate the effect of Internet usage, and of pornography consumption specifically, on the marital status of young men. We show that increased Internet usage is negatively associated with marriage formation. Pornography consumption specifically has an even stronger effect. Instrumental variables and a number of robustness checks suggest that the effect is causal.
Keywords: J12; O33; 330; pornography; divorce; marital formation